Clinical Terminology in Patient Health Record System - SNOMED CT Overview - Ika Novita Dewi (979-26-0263-1)
Background of study: Patient Health Record System (PHRS) is used byphysicians for capturing patient medical records in electronic media.Standardization in PHRS arises a major challenge due to its complexities. Theused of clinical terminology is needed in order to facilitate more expressiveclinical data input, provide unambiguous encoding and support the exchange ofclinical information. One of highly specialized clinical terminology is SNOMEDCT(Systematized Nomenclature of Medicine Clinical Terms) that able to encodeclinical data, and contains concepts that linked to clinical knowledge to enableaccurate recording of data without ambiguity. The aims of this paper is to discussthe use of clinical terminology in PHRS and identifying importance factors forapplying clinical terminology in healthcare services.Method: This study used review of literature in order to find the use of clinicalterminology in patient health record system by reviewing current used of clinicalterminology.Result: The result of the study found that clinical terminology supportsinformation exchange between healthcare providers.